Constitutive modeling for thermo-mechanical low-cycle fatigue-creep stress–strain responses of Haynes 230. (November 2017) - Ahmed, Raasheduddin; Hassan, Tasnim
Highlights: Unified constitutive modeling for thermomechanical fatigue-creep (TMFC) responses. Illustration of the need of advancing constitutive modeling for TMFC responses. Experimental validation of the modified model against a broad set of TMFC responses. Discussion and performance illustration of the modified modeling features. Demonstration of significant progress in unified constitutive modeling. Abstract: Haynes 230 (HA 230), a Nickel-based superalloy, is the primary material of combustor liners in airplane gas turbine engines. This component operates in the temperature range between ambient to as high as 1000  °C. Such thermal cycles together with the resulting strain cycles in a combustor liner may induce thermo-mechanical fatigue-creep (TMFC) damage and initiate cracks earlier than the estimated life. Use of a robust unified constitutive model (UCM) for nonlinear analysis based design may improve fatigue life estimation of high temperature components. Available UCMs in the literature or commercial software packages are unable to simulate the TMFC responses reasonably. Hence, this study developed a UCM incorporating the modeling features of rate and temperature dependence, static-recovery, various kinematic hardening evolutions, and strain-range dependence, and validated the model against a broad set of TMFC experimental responses of HA 230. This modified UCM is capable of simulating the mean-stress evolution under both the out-of-phase and in-phase TMFC loading cycles. The modified UCM can adequately simulate most of the characteristic cyclic phenomena of HA 230 including the influence of maximum temperature on the out-of-phase and in-phase TMFC hysteretic responses, stress amplitude, and stress relaxation during strain-dwell. The time-derivative of the elastic modulus is an essential modeling feature for accurately simulating the inelastic strains under TMFC loading. These simulations demonstrate the progresses made in UCM.